Lobo Antunes: from Naturalism to Posthumanism - Ermelinda Maria Araújo Ferreira (Gragoatá, 2013)
Queer Theory emerged in the United States in the late 1980s, as opposed to sociological studies about gender. Appearing in departments not directly linked to social investigation – as in Philosophy and Literary Criticism –, queer studies problematize classical conceptions of identity, drawing on the concepts and methods in the works of Michel Foucault and Jacques Derrida that propose a break with the Cartesian conception of the humanist subject as the basis of a posthuman ontology. Dealing with theoretical approaches whose boundaries are still diffuse and gather little consensus as to the legitimacy of their effective use, this paper seeks to account for the extreme challenges posed to literary criticism by Lobo Antunes’s novel Que farei quando tudo arde?.